A Randomized Trial Assessing the Safety, Pharmacokinetics, and Efficacy During Morning Off of AZ‐009. Issue 4 (20th January 2022) - Thijssen, Eva; den Heijer, Jonas; Puibert, David; Moss, Laurence; Lei, Mingzu; Hasegawa, David; Keum, Kyo; Mochel, Ken; Ezzeldin Sharaf, Mohammed; Alfredson, Tom; Zeng, Wenxiang; van Brummelen, Emilie; et al.
ABSTRACT: Background: Inhalation of apomorphine could be a faster‐acting and more user‐friendly alternative to subcutaneous injection for treating off periods in Parkinson's disease (PD). Objective: The aim of this study was to compare the safety and pharmacokinetics of inhaled apomorphine (AZ‐009) with subcutaneous apomorphine (APO‐go PEN) in healthy volunteers (HVs) and to examine the safety, pharmacokinetics, and efficacy of AZ‐009 in patients with PD. Methods: In part A of this study, eight HVs received 1 mg AZ‐009 and 2 mg subcutaneous apomorphine in a randomized crossover manner. In the subsequent single ascending dose parts in HVs (part B, n = 16) and patients with PD (part C, n = 25), participants were randomized to placebo or AZ‐009 up to 4 mg. In patients, after medication withdrawal, Movement Disorder Society‐Unified Parkinson's Disease Rating Scale part III and on/off states were assessed predose and postdose. Results: AZ‐009 was rapidly absorbed with peak plasma concentrations at 2 minutes, as compared to 30 minutes for subcutaneous apomorphine. Adverse events for AZ‐009 were comparable to subcutaneous apomorphine, except for mild and transient throat irritation. Adverse events limited AZ‐009 dose escalation in HVs to 3 mg. Patients tolerated up to 4 mg. In patients with PD, 2, 3, and 4 mg AZ‐009 reduced mean Movement Disorder Society‐Unified Parkinson's Disease Rating Scale part III score (standard deviation) by 10.7 (13.6), 12.8 (7.9), and 10.3 (3.7) points, respectively, compared to 4.8 (4.9) after placebo at 10 minutes postdose. The percentage of patients achieving full on within 45 minutes postdose increased dose dependently: 0% (placebo), 17% (2 mg), 50% (3 mg), and 83% (4 mg). Conclusions: AZ‐009 appears to be a rapid‐acting and reasonably well‐tolerated formulation for treating off periods. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society